Epstein-Barr Virus-Encoded Latent Membrane Protein 1 Impairs G2 Checkpoint in Human Nasopharyngeal Epithelial Cells through Defective Chk1 Activation - Deng, Wen; Pang, Pei Shin; Tsang, Chi Man; Hau, Pok Man; Yip, Yim Ling; Cheung, Annie L. M.; Tsao, Sai Wah (PLOS ONE, 2012)
Nasopharyngeal carcinoma (NPC) is a common cancer in Southeast Asia, particularly in southern regions of China. EBV infection is closely associated with NPC and has long been postulated to play an etiological role in the development of NPC. However, the role of EBV in malignant transformation of nasopharyngeal epithelial cells remains enigmatic. The current hypothesis of NPC development is that premalignant nasopharyngeal epithelial cells harboring genetic alterations support EBV infection and expression of EBV genes induces further genomic instability to facilitate the development of NPC. The latent membrane protein 1 (LMP1) is a well-documented EBV-encoded oncogene. The involvement of LMP1 in human epithelial malignancies has been implicated, but the mechanisms of oncogenic actions of LMP1, particularly in nasopharyngeal cells, are unclear. Here we observed that LMP1 expression in nasopharyngeal epithelial cells impaired G2 checkpoint, leading to formation of unrepaired chromatid breaks in metaphases after γ-ray irradiation. We further found that defective Chk1 activation was involved in the induction of G2 checkpoint defect in LMP1-expressing nasopharyngeal epithelial cells. Impairment of G2 checkpoint could result in loss of the acentrically broken chromatids and propagation of broken centric chromatids in daughter cells exiting mitosis, which facilitates chromosome instability. Our findings suggest that LMP1 expression facilitates genomic instability in cells under genotoxic stress. Elucidation of the mechanisms involved in LMP1-induced genomic instability in nasopharyngeal epithelial cells will shed lights on the understanding of role of EBV infection in NPC development.